Ultra‐Clean Isotope Engineered Double‐Walled Carbon Nanotubes as Tailored Hosts to Trace the Growth of Carbyne. (7th August 2022) - Cui, Weili; Simon, Ferenc; Zhang, Yifan; Shi, Lei; Ayala, Paola; Pichler, Thomas
Abstract: A unique scope of mechanical, optical, and electrical properties makes the 1‐D allotrope of carbon, carbyne, one of the most promising materials for applications in various fields. Despite the important progress in the synthesis of carbyne confined to double‐walled carbon nanotubes (DWCNTs), its formation and growth mechanisms remain elusive. Here, it is shown how a rational design of isotope‐engineered ultra‐clean DWCNTs with 13 C‐enriched inner walls—which act as precursors and as tailored hosts—can trace the growth mechanism of confined carbyne upon high‐vacuum annealing at high temperatures. It is unambiguously proven that an exchange of C atoms between the inner and outer tubes takes place, and it is distinguished from the growth of confined carbyne. The latter only happens after the ultra‐clean DWCNT hosts react by partial oxidation yielding encapsulated carbonaceous products, which are well‐defined precursors for the carbyne synthesis with a record of ≈28.8% 13 C enrichment. Tracing the synthesis of carbyne and disentangling it from concomitant high‐temperature processes like healing, reorganization and regrowth of DWCNTs are a crucial step towards accessing the full application potential of confined carbyne hybrids by tailoring the isotopic fillers, as well as the inner and outer tubes of the DWCNT hosts. Abstract : Isotope engineered double‐walled carbon nanotubes enable to trace the growth of carbyne, allowing to identify the precursor and reveal the formation mechanism of confined carbyne, as well as experimentally determine for the first time the theoretical predicted exchange of carbon atoms between the inner and outer tubes.